Livonia, Rus' and the Baltic Crusades in the thirteenth century - Selart, Anti, 1973- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2015)
This monograph by Anti Selart is the first comprehensive study available in English on the relations between northern crusaders and Rus'. Selart re-examines the central issues of this crucial period of establishing the medieval relations of the Catholic and Orthodox worlds like the Battle on the Ice (1242) and the role of Alexander Nevsky using the relevant source material of both “sides”. He also considers the wide context of the history of crusading and the whole Eastern and Northern Europe from Hungary and Poland to Denmark, Finland, and Sweden in 1180-1330. This monograph contests the existence of the constitutive religious conflict and extensive aggressive strategies in the region – the ideas which had played a central role in modern historiography and ideology.